عہدِ رسالت مآبﷺ میں سماجی انصاف اور فلاحِ معاشرہ ۔۔۔عہد بعہد ارتقاء: Social Justice and Welfare of Society in the Era of Prophet (Peace be Upon Him) … Historical Evolution - Dr. Nisar Ahmad (Seerat Studies, 2023)
The development of social justice and welfare of society is an evolutionary process based on consistent effort. This paper intends to trace out the evolutionary process of development of social justice and welfare of society in the era of the Prophet (Peace be Upon Him) by discussing the initiatives taken by the prophet (Peace be Upon Him) in this regard in historical perspective. The article discusses the above mentioned evolutionary process by analyzing the major initiatives taken by the prophet (Peace be Upon Him) in Makkan and Medinian era for the establishment of social justice and welfare of society and trace out the practical guidance for the establishment and development of a society based on social justice and welfare.